Single‐Calibration Cell Size Measurement With Flow Cytometry - Davies, Philip; Cavallaro, Massimo; Hebenstreit, Daniel (Cytometry. Part A, 2025)
ABSTRACT Measuring the size of individual cells in high‐throughput experiments is often important in biomedical research and applications. Nevertheless, popular tools for high‐throughput single‐cell biology, such as flow cytometers, only offer proxies of a cell's size, typically reported in arbitrary scales and often subject to changes in the instrument's settings as selected by multiple users. In this paper, we demonstrate that it is possible to calibrate flowcytometry laser scatter signals with accurate measures of cell diameter from separate devices and that the calibration can be conserved upon changes in the laser settings. We demonstrate our approach based on flow cytometric sorting of cells of a mammalian cell line according to a selection of scatter parameters, followed by cell size determination with a Coulter counter. A straightforward procedure is presented that relates the flow cytometric scatter parameters to the absolute size measurements using linear models, along with a linear transformation that converts between different instrument settings on the flow cytometer. Our method makes it possible to record on a flow cytometer a cell's size in absolute units and correlate it with other features that are recorded in parallel in the fluorescence detection channels.